STUDENTS' PREFERENCES TOWARDS SHARIA FINANCIAL PRODUCTS: A QUALITATIVE STUDY AND CONSUMER LOYALTY MODEL DEVELOPMENT - Sudana Sudana; Muhammad Jagat Dermawan (Journal of Golden Generation Economic, 2026)
This study aims to identify and analyze college students' preferences for Islamic financial products, explore the influence of these preferences on loyalty formation, and develop a conceptual model of Islamic financial consumer loyalty. The research method used was qualitative with a phenomenological approach. Data were collected through semi-structured interviews with 17 college students who had knowledge or experience related to Islamic financial products. Data analysis was performed using NVivo software. The results showed that college students' preferences were influenced by religiosity, financial institution reputation, trust, digital service innovation, and financial education. These factors contribute to the formation of consumer loyalty. Based on these findings, this study developed a consumer loyalty model that encompasses three main dimensions: spiritual attachment, digital engagement, and community-based advocacy. This model integrates consumer loyalty theory and Value-Belief-Norm (VBN) theory to explain the relationship between religious values, digital behavior, and loyalty to Islamic financial products. The implications of this research lie in its contribution to broadening the theoretical understanding of consumer loyalty in the Islamic financial sector and providing strategic direction for financial institutions in strengthening long-term relationships with young customers.